Enhanced irradiation-resistance in NbMoTaW refractory high-entropy alloy via rhenium addition - Li Huang; Shuo Sun; Jianrong Xue; Xiaohui Lin; Xuanqiao Gao; Yanchao Li; Jianfeng Li; Chunfang Ma; Wen Zhang (Heliyon)
The He2+ irradiation-induced mechanical and microstructural evolutions were studied in Nb25Mo25Ta25W25 (at.%) and Nb20Mo20Ta20W20Re20 (at.%) refractory high-entropy alloys (RHEAs) films, respectively. The addition of Re reduces the yield stress, while improves the ductility in as-deposited NbMoTaW RHEA film. After He2+ irradiation at room temperature, grain boundary brittleness is much severe in NbMoTaW RHEA film than in NbMoTaWRe RHEA film. The addition of Re enhances lattice distortion, leading amorphous regions with several nanometers forms in the grain boundaries in NbMoTaWRe RHEA film. In additionn, grain sizes in NbMoTaWRe RHEA are much smaller than in NbMoTaW RHEA. Excess volumes facilitate the annihilation of damages caused by He ions bombardment. He bubbles mainly distributes along grain boundaries in NbMoTaW RHEA film. The bubble size decreases and becomes hard to discern in NbMoTaWRe RHEA film. Thus, hardening effect induced by He irradiation is less obvious in NbMoTaWRe than in NbMoTaW RHEA film. In summary, the addition of Re to NbMoTaW RHEA effectively improves irradiation-resistance.